Effects of COD/TN ratio and loading rates on performance of modified SBRs in simultaneous removal of organic matter and nitrogen from rubber latex processing wastewater - Nam, Duong Van; Chau, Nguyen Hoai; Tatsuhide, Hamasaki; Vien, Dinh Van; Hung, Phan Do (Vietnam Journal of Science and Technology, 2018)
Two modified sequencing batch reactors (SBRs) specially configured to consist of both oxic and anoxic zones, and be operated with only a single simultaneous oxic/anoxic phase in each treatment batch were tested to evaluate their applicability in treatment of rubber latex processing (RLP) wastewater. The former, R1 was operated with constant aeration, whereas the latter, R2 was operated with air flow varied from lower rate in the early period of the reaction phase to higher rate in the later one. Effects of the chemical oxygen demand (COD) to total nitrogen (TN) ratio and their loading rates on performance of the modified SBRs in simultaneous removal of organic matter and nitrogen from RLP wastewater were investigated. It was observed that performance of the two reactors in removal of COD and ammonium nitrogen was similar, and did not remarkably change when varying COD/TN ratio, as well as COD and TN loading rates in the ranges of 3.4 – 6.0 gCOD/gN, 0.8 – 1.7 kgCOD×m-3×d-1 and 0.15 – 0.34 kgN×m-3×d-1, respectively. The average COD removal efficiencies were over 95%. Ammonium nitrogen was almost completely eliminated in both reactors with effluent concentrations lower than 1.0 mg/L. Nevertheless, TN removal efficiencies of both reactors were significantly increased with increasing the COD/TN ratio from 3.4 to 6.0, and slightly decreased when increasing the TN loading rate from 0.15 to 0.34 kgN×m-3×d-1. The most effective COD/TN ratios were in the range of 5 – 6, at which the maximal TN removal efficiencies of R1 and R2 were 92% and 97%, respectively.